A MINOR STUDY ON MAIN DIFFICULTIES IN LEARNING LISTENING SKILLS PERCEIVED BY FIRST-YEAR STUDENTS OF FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION, ULIS, VNU - Nguyễn, Thị Thu Thảo (2021)
Listening comprehension plays a significant role in daily communication and in educational process. In spite of its importance, the state of teaching and learning listening has long been ignored, especially in rural areas in Vietnam. A large number of students, who come from countryside, suffer a serious disturbance in learning listening when entering university. The present study attempts to investigate the listening problems perceived by first-year students of FELTE, ULIS, VNU. To address the research problems, the paper used questionnaire and semi-structured interview as the main research instruments to collect data. Brief descriptions of participants as well as the data collection methods also were provided. The results of the study reveal that the majority of listening comprehension difficulties pertaining to four main categories: the speakers, the listeners, the materials, and the physical setting. In accordance with exploring the hindrances, some learning strategies employed by freshmen are introduced as well. Based on the findings of the study, some pedagogical implications are proposed for teachers and students in their teaching and learning listening skill